2001
DOI: 10.1038/sj.bdj.4801122
|View full text |Cite
|
Sign up to set email alerts
|

Caries incidence following restoration of shortened lower dental arches in a randomized controlled trial

Abstract: Two years after restoration of lower shortened arches for an elderly sample of patients, there was a significantly greater incidence of new and recurrent caries lesions in subjects restored with RPDs compared with cantilever RBBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 19 publications
11
105
0
2
Order By: Relevance
“…Two RCTs found that caries developed more frequently after treatment with RPDs compared to CFPD treatment [35,39]. Gingival inflammation and plaque accumulation on abutment teeth of RPDs were higher than those of CFPDs 2 and 5 years after treatment, while probing pocket depth, tooth mobility and alveolar bone height were almost identical for both treatments [40,41].…”
Section: Abutment Teeth and Periodontal Tissuementioning
confidence: 91%
See 2 more Smart Citations
“…Two RCTs found that caries developed more frequently after treatment with RPDs compared to CFPD treatment [35,39]. Gingival inflammation and plaque accumulation on abutment teeth of RPDs were higher than those of CFPDs 2 and 5 years after treatment, while probing pocket depth, tooth mobility and alveolar bone height were almost identical for both treatments [40,41].…”
Section: Abutment Teeth and Periodontal Tissuementioning
confidence: 91%
“…However, there was no statistically significant difference in the patient satisfaction between patients with RPDs and those with CFPDs [36]. An RCT found that OHRQoL improved after treatment with RPDs, while no statistically significant difference was found between patients with RPDs and those with CFPDs due to small sample size [33].…”
Section: Patients Satisfaction and Qolmentioning
confidence: 97%
See 1 more Smart Citation
“…62,64 In a randomised controlled trial that compared the use of RPDs or single pontic cantilever resin-bonded fixed partial dentures to restore severely shortened mandibular arches, there were significant improvements in satisfaction scores for both treatments but a larger clinical effect for the fixed partial denture group. 65 In a somewhat underpowered cross-sectional study, it was found that patients with shortened dental arches only perceived a benefit of RPD provision to their quality of life if the RPD included replacement of missing anterior teeth. 66 There was no perceived benefit from the use of RPDs if only posterior teeth were replaced.…”
Section: Impact Of Rpds On Quality Of Lifementioning
confidence: 98%
“…The effect of molar support loss on the migration of the remaining teeth, 1,2 possible interactions with temporomandibular disorders, 3,4 and chewing functions 5,6 has been assessed extensively. The results of these studies generally suggest that, following the loss of molar teeth, an initial, minor migration of the remaining teeth may lead to a new occlusal equilibrium.…”
Section: Introductionmentioning
confidence: 99%